IMPROVEMENT OF INNOVATION STRATEGIES FOR BANK DEVELOPMENT - Ковальчук , Вероніка; Орліков, Дмитро; Орлікова, Вікторія (Socio-economic relations in the digital society, 2019)
The bank of the future greatly needs effective innovative activity of banks today, including — the effective investment in technological improvement of remote banking services, the formation of a high quality credit portfolio, the creation of conditions for further development of a banking institution. In this regard, the issue of enhancing innovative strategies of bank development is of particular importance, and determines the chosen topic relevant. The purpose of the article is to investigate the theoretical and methodological foundations of the bank’s strategic development management and to formulate the scientific and practical recommendations for increasing efficiency of innovation activity of the modern bank. It is determined that the issue of the strategic development in bank should be closely connected to the introduction of innovative technologies. The types and directions of application of certain digital technologies are analyzed, as well as the readiness of the personnel to effectively implement the digital model of bank development with the help of the latest technologies. It was emphasized that today, banks are undergoing a revolution in products, services and delivery methods, customer identification and communication technologies, biometric technologies to enhance security and reliability of identification. Therefore, the bank of the future is a bank that is «always in touch» and «always ready» to serve the client, understands well the needs of its clients, actively develops and implements contactless locally oriented payment technologies and has a perfect organization of the back-office service, providing customers with services remotely and through innovative affiliates / branches. Formulation of an innovative strategy in the direction of Bank 3.0 is proposed as the most effective way to achieve maximum development of a banking institution in the current conditions.